Produção de cultivares de milho em função de adubações e espaçamentos entre linhas - Alves, Anailson de Sousa (Universidade Federal Rural do Semi-Árido, 2015)
The production potential of maize can be exploited by the judicious implementation of technical aspects, such as the choice of cultivar that best suits growing conditions, spacing employ and proper management. The objective was to evaluate the agronomic performance, yield components and yield of two maize cultivars for different types of fertilization and row spacing an irrigated cropping system. The experiment was conducted at the Experimental Farm Rafael Fernandes, in Mossoro, RN, adopting a randomized complete block design in a factorial 3 x 2 x 2, with four replications. Treatments consisted of three fertilizer (AO - Organic fertilization; AOM - fertilization and organic-AM - Mineral fertilization), two corn cultivars (Bras 3010 and Potiguar) and two row spacings (80 cm and 50 cm). We evaluated the emergency speed index, initial and final plant population, spikes insertion height, stem diameter, number of kernel rows per ear, number of grains per ear, ear yield with and without straw, spike diameter, spike length, grain weight per ear and yield. The organic-fertilizer (AOM) showed no significant differences in relation to mineral fertilization (M) in the parameters of agronomic performance of maize cultivars increased, except for stem diameter. The agronomic aspects of corn cultivars were evaluated using the incremented spacing of 80 cm between rows, except the initial and final population of plants. The highest yield was obtained with the use of organic fertilizer in cultivar Potiguar, spaced at, 80 cm between rows. The final population, yield and thousand grain weight were the components that most influenced the evaluation of all the data. Each corn cultivar evaluated responded differently to fertilization and evaluated spacings. The agreement between the results of cluster analysis and principal component analysis with the analysis of variance shows the appropriateness of multivariate statistical techniques used in this study. The combined use of multivariate techniques allowed to infer more safely about groups formed between treatments and their characteristics
Production of maize cultivars as a function of fertilization and row spacings
Keywords: Corn; Organic-mineral fertilization; Crop production; Spatial arrangement; Milho; Adubação organomineral; Produção agrícola; Arranjo espacial; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO